Respon Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium Cepa L.) Varietas Bima pada berbagai Komposisi Media Tanam - Astuti Kurnianingsih; Susilawati Susilawati; Rifki Hayatullah (Seminar Nasional Lahan Suboptimal, 2018)
Kurnianingsih et al, 2019. Growth and Yield of Shallot (Allium  Cepa  L.) Bima Variety on Several Composition of Planting Media. pp. 120-128.Shallot (Allium cepa L) is a kind of vegetable horticultural commodities which have long been cultivated by farmers intensive horticulture development issues and challenges that often disrupt macro economic stability is chili and shallot. In Indonesia, Sentra shallot production in the provinces of Central Java, East Java, West Java and West Nusa Tenggara. The medium of planting is one of the main factors that affecting plant growth. The organic material as a growing medium usefull to increasing the textureof the soil, in order to achieving the appropriate planting culture. This research will be carried out in the garden and the Experimental Laboratory of Plant Physiology Department of Agriculture Faculty of Agriculture, Sriwijaya of University Indralaya. This study has began in October 2016 - January 2017. The study was laid out by Randomized Block Design with 6 treatment and 5 replication, Each unit consists of 3 treatment plants, so there are 90 plants. The media are A0: Soil, A1: Soil: Fertilizers from oil palm empty fruit bunches (TKKS) (2: 1), A2: soil: chicken manure (2: 1), A3: Soil: cow manure (2: 1), A4: soil: chicken manure: Fertilizer from oil palm empty fruit bunches  (TKKS) (2: 1: 1), A5: soil: Cow manure: Fertilizer from oil palm empty fruit bunches (TKKS) (2: 1: 1). The measurement variables are plant height, number of leaf per panicle, number of tillers per hill, number of tuber per hill,  weight of fresh tuber per hill, weight of tuber dry per hill. The results that the growing media consisting of soil and chicken manure with a ratio of 2: 1 (v: v) is best for growth and the highest yield of shallot.